Electrocatalytic Disproportionation of Nitric Oxide Toward Efficient Nitrogen Fixation. Issue 14 (15th February 2023) - Wu, Angjian; Lv, Jiabao; Xuan, Xiaoxu; Zhang, Jinhe; Cao, Ang; Wang, Mengjie; Wu, Xiao‐Yu; Liu, Qian; Zhong, Yunhao; Sun, Wei; Ye, Qiulin; Peng, Yaqi; et al.
Abstract: Electrocatalytic conversion of waste nitric oxide into ammonia is a promising approach to achieve sustainable nitrogen fixation. Herein, a CoNi co‐oxides catalyst is designed for NH3 electrosynthesis with the merits of facilitating NO adsorption and reducing the reaction energy barrier. By synergistic coupling with anodic NO oxidation, electrocatalytic disproportionation of NO is first realized to simultaneously synthesize value‐added double nitrogen products (NH3 and nitrate) with increased total energy efficiency. Furthermore, decoupled acid–base asymmetric electrolyte design is proposed in a united assembled electrolyzer, enabling a high NH3 production rate (26.27 mg h −1 cm −2 ) with unit faradaic efficiency and a remarkable nitrate production rate of 68.41 mg h −1 cm −2 at the anode. A low cell voltage of 3.58 V is obtained by optimizing ion agglomeration within the membrane to promote the charge‐ion exchange and electrode kinetics. Technoeconomic analysis demonstrates the economic feasibility of recycling waste NO by the electrocatalytic disproportionation strategy. Abstract : Electrocatalytic disproportionation of nitric oxide is achieved in a bipolar membrane based electrolysis system with decoupled acid–base electrolytes, which aims for efficient nitrogen fixation via coupling the cathodic NO reduction reaction with the anodic NO electrooxidation simultaneously.